2015
DOI: 10.1016/j.phytochem.2015.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid metabolism is strikingly different between pollen and leaf in Arabidopsis as revealed by compositional and gene expression profiling

Abstract: Although sphingolipids are essential for male gametophytic development in Arabidopsis thaliana, sphingolipid composition and biosynthetic gene expression have not been previously examined in pollen. In this report, electrospray ionization (ESI)-MS/MS was applied to characterization of sphingolipid compositional profiles in pollen isolated from wild type Arabidopsis Col-0 and a long-chain base (LCB) Δ4 desaturase mutant. Pollen fractions were highly enriched in glucosylceramides (GlcCer) relative to levels prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…15 The significance of this remains to be determined. We recently showed that GIPCs are the major lipids of the tobacco (Nicotiana tabacum) highly-purified PM, and can reach up to 40 mol% of total lipids, whereas gangliosides represent only few percent of animal PM, e.g.…”
Section: Sphingolipids: Crucial Elements In Membrane Organizationmentioning
confidence: 99%
“…15 The significance of this remains to be determined. We recently showed that GIPCs are the major lipids of the tobacco (Nicotiana tabacum) highly-purified PM, and can reach up to 40 mol% of total lipids, whereas gangliosides represent only few percent of animal PM, e.g.…”
Section: Sphingolipids: Crucial Elements In Membrane Organizationmentioning
confidence: 99%
“…The emerging lipid metabolomic approach called lipidomics is a powerful tool to demonstrate dynamics of lipid metabolism and to identify new lipid classes associated with various biological functions (Retra et al ., ; Burgos et al ., ; Degenkolbe et al ., ; Liu et al ., ; Okazaki et al ., , ; Vu et al ., ), whereas GIPC species have remained insufficiently or not detected due to their poor recovery in the solvent systems optimized for glycerolipid extraction. However, recent analytical advances focusing on sphingolipids have been yielding comprehensive sphingolipid profiles, especially in Arabidopsis and other dicotyledonous plants (Markham et al ., ; Markham and Jaworski, ; Chen et al ., 2008; Wang et al ., ; Chen et al ., 2011; Markham et al ., ; Kimberlin et al ., ; Nagano et al ., ; Luttgeharm et al ., ). Sphingolipid structures are estimated to vary among different plant tissues and species (Markham et al ., ; Buré et al ., , ; Blaas and Humpf, ; Cacas et al ., ; Tellier et al ., ), but sphingolipidomic profiles in monocots remain to be addressed.…”
Section: Introductionmentioning
confidence: 97%
“…In most Arabidopsis tissues, the major GIPC glycosylation consists of one hexose (Hex) attached to GlcA linked to IPC (Hex-GlcA-IPC), while in seeds, the dominant GIPC contains an amino sugar linked to the GlcA (Tellier et al, 2014). A recent report found that Arabidopsis pollen GIPCs also have a different glycosylation pattern, consisting of a complex array of N-acetyl-glycosylated GIPCs, including species with up to three pentose units (Luttgeharm et al, 2015). Other plant tissues, such as tobacco (Nicotiana tabacum) leaves, do not contain the Hex-GlcA-IPC found in Arabidopsis but instead the dominant structure consists of GlcNAc attached to the GlcA linked to IPC (Carter et al, 1958;Kaul and Lester, 1975;Hsieh et al, 1981;Buré et al, 2011).…”
Section: Introductionmentioning
confidence: 99%